Implementasi Enterprise Resource Planning (ERP) Odoo untuk Manajerial Akuntansi TPA Al-Muhajirin - Ayu, Gita Sekar; Rafi, Javier Alrizal; Oktaviani, Mela (Journal Of Computer Science Contributions (JUCOSCO), 2023)
The TPA Al-Muhajirin is one of the educational institutions or vessels that foster child welfare. This TPA Al-Muhajirin provides a reading instruction on the Qur’an agreed at an early age and also understands what is the basis of the dinul islam. As time went by, the TPA Al-Muhajirin recognized that there was a lack of accounting and inventory recording systems. Thus, there is a high need for a technology that can improve the system. Odoo represents an open-source equipped with complete features. Odoo is considered highly effective to be used as a solution to address business issues. Odoo contains a myriad of modules, the modules that will be used to support the accounting and inventory logging process in the TPA Al-Muhajirin are Accounting and Inventory. With this Odoo present, the process of accounting and inventory has become more effective, systematically aligned, and highly efficient.